10 - Lessons from an ethnographic encounter with young women in a South African Township: Sinethemba S. Sidloyi - Sinethemba S. Sidloyi, (African Sociological Review, 2021)
This paper discusses lessons from the researcher’s experiences of her ethnographic approach that employed a sociological study on the lived experiences of young women in Ngangelizwe Township, Mthatha to uncover the various ways in which the young women negotiated their lifestyles. The ethnographic research approach is underpinned by the desire to gain an in-depth understanding of the participants lived experiences. Such understanding is intended to go beyond the participant’s explicit identifications of their realities, unearthing the hidden meanings shaping the production of their social action. However, gaining access into the lives of participants is not a straightforward process and should be recognised in its difference from gaining access into the area of study. Gaining access into the social lives of participants and engaging in ethnographic observations is a complex process in which the researcher participates in multiple overlapping roles that are shaped by unforeseen on-field occurrences. This paper sheds light on some of the field occurrences in how they informed the data collection process through which the objective of examining the realities of young women in Ngangelizwe Township was achieved.